2020
DOI: 10.1186/s12884-020-03245-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use and experience of an infant feeding genogram to facilitate an assets-based approach to support infant feeding

Abstract: Background A lack of perceived social support influences women’s infant feeding behaviours. The Infant Feeding Genogram is a visual co-constructed diagram which details people/services that can provide support to women and can facilitate a connection between mothers and their existing assets landscape. The aim of this study is to explore women’s and infant feeding helpers’ experiences and use of an infant feeding genogram delivered to the intervention group of the “Assets-based infant feeding h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A strategy to help facilitate these behaviors is through assetsbased approaches, ensuring information is readily available and through peer support interventions. The ABA feasibility study and ongoing ABA-feed trial explicitly encourage women to access information and support through their personal, social and community networks (Clarke et al, 2020a;Ingram et al, 2020;Thomson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strategy to help facilitate these behaviors is through assetsbased approaches, ensuring information is readily available and through peer support interventions. The ABA feasibility study and ongoing ABA-feed trial explicitly encourage women to access information and support through their personal, social and community networks (Clarke et al, 2020a;Ingram et al, 2020;Thomson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The ABA study explored the feasibility, acceptability, and utility of a new model of peer support. The model was underpinned by behavior change theory and offered an assets-based approach that focussed on positive capabilities of individuals and communities, including use of a Genogram (aka friends and family diagram) and assets leaflet (Clarke et al, 2020a;Ingram et al, 2020;Thomson et al, 2020). Trained peer supporters (named Infant Feeding Helpers) provided women with an antenatal contact (∼30-32 weeks gestation), daily support (text, telephone) for 2 weeks immediately after birth, and for ongoing support up to 8 weeks post-natal, with frequency and types of contact organized on a peer-mother negotiated basis (Clarke et al, 2020a,b).…”
Section: Settingmentioning
confidence: 99%
“…To avoid contact with other people due to social distancing requirements, breastfeeding mothers expressed that they had negative feelings and stayed at home with limited social contact with people, resulting in declining social opportunities and support services [ 59 ]. It is vital to provide professional peer and healthcare support, and communication, during the early weeks of breastfeeding for mothers and their babies, to enhance successful breastfeeding [ 60 , 61 , 62 , 63 ]. During the early weeks of breastfeeding, participants of this study who particularly required care terminated breastfeeding due to an absence of practical, emotional, professional peer and healthcare support, and social gatherings.…”
Section: Discussionmentioning
confidence: 99%
“…Genograms have a rich history of being used in clinical settings to assist with collecting family level data on everything from genetic risks (Daly et al, 1999; Samson et al, 2019) to family structures/resources/relationships (Darwent et al, 2016; Liossi et al, 1997; Perez et al, 2010; Watts & Shrader, 1998); and as a tool to personalize family interventions (Abatemarco et al, 2012; Arias, 2017; Clarke et al, 2020; Thomson et al, 2020). Genograms play a role in family research and have demonstrated utility as an assessment tool, and as a means to assess complex topics such as family stress management skills and handling conflict resolution (Leonidas & Santos, 2015), or to understand health status and risk factors across individual, family and community levels (McGuinness et al, 2005).…”
Section: Introductionmentioning
confidence: 99%